A Lyapunov function and global properties for SIR and SEIR epidemiological models with nonlinear incidence - Andrei Korobeinikov; Philip K. Maini (Mathematical Biosciences and Engineering)
Explicit Lyapunov functions for SIR and SEIR compartmentalepidemic models with nonlinear incidence of the form $β I^p S^q$for the case $p ≤ 1$are constructed. Global stability of the models is thereby established.